UJI AKTIVITAS ANTIKOLESTEROL EKSTRAK DAUN KETEPENG CINA (Cassia alata L.) TERHADAP PENURUNAN KADAR KOLESTEROL MENCIT PUTIH JANTAN (Mus musculus L.) - Khoirila, Nisa; Walid, Muhammad (Universitas Imelda Medan, 2024)
High levels of cholesterol in the blood can increase the risk of hypertension, coronary heart disease (CHD), stroke, peripheral artery disease (PAD), and type 2 diabetes. One potential plant for traditional medicine to lower cholesterol levels is Cassia alata L. Cassia alata L. is known to contain flavonoid compounds, suspected to act as cholesterol-lowering agents in the body. This study aimed to determine the anti-cholesterol activity of Cassia alata L. in reducing cholesterol levels in male white mice (Mus musculus L.). The research employed an experimental design, utilizing the maceration method with 96% ethanol as the solvent for extraction. Male white mice aged 3-4 months, weighing 20-30 grams, were used as test subjects. The first group served as the positive control using simvastatin suspension, the second group as the negative control using 0.5% Na CMC solution, the third group received Cassia alata L. extract at a concentration of F1 (10%), F2 (20%), F3 (30%). Data analysis was performed using One Way Anova. The results of the One-way Anova test obtained F count 31.192 > F table 3.48 and sig. value of 0.000 <0.05, so Ho is rejected and Ha is accepted which can be concluded that there is an effect of anticholesterol activity on Cassia alata L. extract. concentration of 10%, 20%, and 30%. Then in the Post Hoc Test using LSD, K (+) showed the same results as F3 (30%) with a significant value of 0.54 so that p>0.05 which showed no significant difference in anticholesterol effectiveness between K (+) and F3 (30%). The results revealed that Cassia alata L. extract at concentrations of 10%, 20%, and 30% exhibited activity in reducing cholesterol levels, which is F3 (30%) demonstrating the most significant cholesterol-lowering effect. This is attributed to the presence of flavonoid compounds in the Cassia alata L. extract.